Dealing with a hot potato: The commemoration of the 1959 “Potato Boycott” (Historia, 2021)
The year 2009 marked the 50th commemoration of the so-called "Potato Boycott". This celebration, not unlike the boycott itself, was shrouded in controversy. While the Mpumalanga provincial government appeared to initiate premature celebrations, the event itself was compounded by various misunderstandings and conflicting interpretations. This article will not only analyse the contested nature of the recent commemoration, but also consider the complexity of the 1959 boycott itself.
Keywords: Potato Boycott; commemoration; African National Congress; Gert Sibande; Bethal; Mbongeni Ngema; farm labour; Michael Scott; Ruth First; Henry Nxumalo; pass laws; apartheid; Aartappelboikot; herdenking; plaasarbeid; paswette